Concomitants of Record Values From a General Farlie-Gumbel-Morgenstern Distribution - Khames, Sohair; Mokhlis, Nahed (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we discuss the distributions of concomitants of record values arising from a polynomial-type single parameter extension of general Farlie-Gumbel-Morgenstern bivariate distribution. We derive the single and the product moments of concomitants of record values generally for any marginal distributions. The results obtained are applied to two-parameters exponential marginal distributions. In this case, we show that the maximal positive correlation between the two variables is approximately =423. Best linear unbiased estimators based on concomitants of record values of some parameters involved in the distribution are derived. Moreover, we obtain predictors of concomitants of record values by two methods. Finally a numerical illustration is presented to highlight the theoretical results obtained.